2018
DOI: 10.1186/s12974-018-1198-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and cytotoxic effects of bifenthrin in primary microglia and organotypic hippocampal slice cultures

Abstract: BackgroundPyrethroids, such as bifenthrin (BF), are among the most widely used class of insecticides that pose serious risks to human and wildlife health. Pyrethroids are proposed to affect astrocytic functions and to cause neuron injury in the central nervous system (CNS). Microglia are key cells involved in innate immune responses in the CNS, and microglia activation has been linked to inflammation and neurotoxicity. However, little information is known about the effects of BF-induced toxicity in primary mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 109 publications
1
22
0
Order By: Relevance
“…Dysregulated pathways involved in maintaining structural stability of the extracellular matrix and impaired focal adhesion in the brains of bifenthrin-exposed trout are consistent with oxidative stress induced effects previously observed in neuronal in vitro cell lines and in murine, in vivo-based studies, following bifenthrin treatment [51][52][53][54], though, interestingly, oxidative stress genes were not differentially altered in bifenthrin treatment groups, relative to controls. Similarly, we previously reported that steelhead trout exposed to 60 and 120 ng/L bifenthrin were predicted to have induced reactive oxygen species production due to oxidative stress, and subsequently observed apoptotic effects driven by altered levels of metabolites [23].…”
Section: Discussionsupporting
confidence: 86%
“…Dysregulated pathways involved in maintaining structural stability of the extracellular matrix and impaired focal adhesion in the brains of bifenthrin-exposed trout are consistent with oxidative stress induced effects previously observed in neuronal in vitro cell lines and in murine, in vivo-based studies, following bifenthrin treatment [51][52][53][54], though, interestingly, oxidative stress genes were not differentially altered in bifenthrin treatment groups, relative to controls. Similarly, we previously reported that steelhead trout exposed to 60 and 120 ng/L bifenthrin were predicted to have induced reactive oxygen species production due to oxidative stress, and subsequently observed apoptotic effects driven by altered levels of metabolites [23].…”
Section: Discussionsupporting
confidence: 86%
“…There are many reports confirming that exposure on pyrethroids causes oxidative stress and in this mechanism causes an increase in the expression of genes encoding proinflammatory cytokines [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The interleukin1β is primarily synthesized in macrophages and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression of COX-2 gene, revealed significant elevations in liver and muscle of treated fish in comparison with the control group. Similarly, Gargouri, Yousif, Bouchard, Fetoui, and Fiebich (2018) showed that exposure of microglial cells to buprofezin, in vitro, resulted in significant induction of protein synthesis and mRNA expression of COX-2.…”
Section: Expression Findings Of Il-1β and Cox-2 Genesmentioning
confidence: 95%